In vitro lipid peroxidation of intestinal bile salt-based nanoemulsions: Potential role of antioxidants. (December 2013) - Courraud, J.; Charnay, C.; Cristol, J. P.; Berger, J.; Avallone, S.
Abstract: Over the last decades, oxidative stress has been described as a deleterious phenomenon contributing to numerous noncommunicable diseases such as cardiovascular disease, diabetes, and cancers. As many authors ascribed the healthy effect of fruit and vegetable consumption mainly to their antioxidant contents, it has been hypothesized that their protection could occur from the gut. Therefore, the aim of this study was to develop an original and physiological model of nanoemulsions to study lipid peroxidation within the intestine and to assess the properties of potential antioxidants in this setting. Several nanoemulsions were compared in terms of physical characteristics and reactivity to 2, 2'-azobis-(2-amidinopropane) hydrochloride (AAPH)-induced oxidation. Formulations included different types of lipids, a detergent (a conjugated bile salt or sodium dodecyl sulfate) and, finally, lipophilic antioxidants. Hemin and myoglobin were also tested as relevant potential oxidants. Fatty acid (FA) peroxidation was monitored by gas chromatography while malondialdehyde and antioxidant contents were measured by HPLC. Investigated nanoemulsions were composed of spherical or cylindrical mixed micelles, the latter being the least resistant to oxidation. In the experimental conditions, AAPH was the only efficient oxidant. Alpha-tocopherol and lutein significantly slowed FA degradation from 4 to 1 μM, respectively. On the contrary, beta-carotene did not show any protective capacity at 4 μM. In conclusion, the tested nanoemulsions were appropriate to assess antioxidant capacity during the intestinal phase of digestion.